The Comparison of Flipped Teaching Method Versus Teacher-Centered in Improving Students' Writing - Haris Islam; Sonny Elfiyanto; M. Inzah (STAI Miftahul Ula Nganjuk, 2023)
This research aimed to investigate flipped versus teacher-centered methods to improve students' writing and to test the teaching method in ten grades of senior high school in Genggong, Indonesia. This method was quantitative, which was an experimental research design. A sample of fifty students was used to assess the effectiveness of these teaching methods for developing students' writing descriptive text. Our findings confirmed a significant difference before and after being taught using flipped versus teacher-centered methods in descriptive writing.